Combined lipiodol marking and video-assisted thoracoscopic surgery in a hybrid operating room - Fumimoto, Satoshi; Sato, Kiyoshi; Koyama, Mitsuhiro; Yamamoto, Kazuhiro; Narumi, Yoshifumi; Hanaoka, Nobuharu; Katsumata, Takahiro (Journal of Thoracic Disease, 2018)
Background: The development of diagnostic technology has led to detection of an increasing number of small pulmonary nodules (SPNs), which can be difficult to locate intraoperatively. Here, we report our experience performing single-stage lipiodol localization and surgical resection in a hybrid operating room (OR). Methods: Between June 2016 and August 2017, 30 patients with 32 SPNs underwent sliding gantry-based multidetector computed tomography (MDCT)-guided lipiodol marking followed by video-assisted thoracoscopic surgery (VATS) in a hybrid OR. After induction of general anesthesia, all nodules were marked with 0.2 mL lipiodol under MDCT fluoroscopic guidance, followed by immediate VATS. Results: The mean SPN diameter and distance from the pleural surface were 10.7±4.5 mm (range, 5.0–21.0 mm) and 18.0±9.0 mm (range, 2.8–32.0 mm) respectively. The MDCT-guided localization procedure required 15.8±6.0 min (range, 8.0–32.0 min). All the nodules were marked with lipiodol and detected during fluoroscopy as a clear spot. The median deviation between the radio-opaque nodule and the target nodule was 7.8±3.6 mm (range, 3.0–20.0 mm). In two cases, MDCT scans performed after completion of marking revealed mild pneumothorax, which did not need further intervention. VATS resection was converted to thoracotomy in two patients because of strong pleural adhesions and intraoperative bleeding from the pulmonary vein. No other complications occurred during the combined approach, and there was no intra- or post-operative mortality or morbidity. Conclusions: These results suggest that a combined approach using MDCT-guided lipiodol marking followed by VATS is feasible and has acceptable accuracy in resection of SPNs.